Employee share options and the equity-liability distinction: a way forward? - Wallington, Craig (My University, 2014)
This paper explores the distinction between ‘equity’ and ‘liabilities’ in financial reporting in order to assess the merits of the current system of accounting for share-based payment transactions. It applies an interpretive methodology. Data were collected from a series of interviews with purposefully selected experts. Criticisms of and support for the current accounting regime are interpretively analysed and used to identify key themes or principles for evaluating the merits of three models proposed in the academic literature: the strict liability, narrow equity and ownership-settlement models. The study finds that the strict liability approach remains supported on the grounds that it provides decisionuseful information with which users are familiar. The other models are rejected as they are perceived as diminishing the usefulness of financial reporting. The study also identifies support for an obligation-centric approach, not fully developed in the literature, which may require detailed consideration by standard-setters. Overall, these findings will be useful for both practitioners and academics grappling with the difficulty of defining ‘equity’ and ‘liabilities’. In addition, the research makes a valuable contribution by addressing the need for interpretive-inspired financial reporting research. To the best of the author’s knowledge, this thesis is also the first South African study to investigate the appropriate classification criteria for instruments such as share-based payments and provide normative recommendations for the International Accounting Standards Board.
Keywords: Financial reporting; Equity; Liabilities